TRAINING OF TEACHERS OF PHYSICAL EDUCATION: HUMAN MOTRICITY IN CHILDREN (Fiep Bulletin - online, 2019)
The present article aims to analyze the practice of Human Motricity in Physical Education classes in Early ChildhoodEducation.An in-depth study on Human Motricity will be done to insert or deepen this new paradigm in Physical Education classes, sothat this will occur in an innovative way in the studies on Human Motricity.In order for this change to take place, the study on Human Motricity will have to be started in the undergraduate course,perfected and developed to be reproduced effectively in Early Childhood Education.Having as pedagogical support the qualitative research, approaching the participation of the subjects involved, and thusbecoming an exploratory descriptive research, being carried out in a school of the Municipal Network of Early Childhood Educationand Elementary School in the Municipality of Ponta Grossa - Pr.Note that in the Municipality of Ponta Grossa the discipline of Physical Education is not included in the curriculum of InfantEducation, having only in elementary schools that have classes of Early Childhood Education, even contained in LDB 9394/96,emphasizing the importance of motor development in Early Childhood Education.Thus, this project aims to answer the following question: what contributions can the activities of Human Mobility offer to thestudents of Early Childhood Education of a Municipal School of Ponta Grossa?Therefore, Physical Education aims to increase the chances of Human Mobility by means of motor conducts, instigatingthe realization of movements that can contribute to the integral development of the child, being understood as a support for PhysicalEducation classes in Early Childhood Education.
Keywords: Human Mobility; Early Childhood Education; Teacher Training